2013
DOI: 10.1517/14712598.2014.859673
|View full text |Cite
|
Sign up to set email alerts
|

Role of periostin, FENO, IL-13, lebrikzumab, other IL-13 antagonist and dual IL-4/IL-13 antagonist in asthma

Abstract: Lebrikizumab block IL-13 signaling through the IL-13Rα1/IL-4Rα receptor. There was a larger reduction in FENO in the high periostin subgroup than in the low periostin subgroup (34.4 vs 4.3%). Serum CCL17, CCL13 and total IgE levels decreased in the lebrikizumab group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…Although the mechanisms of periostin in AERD are not fully understood, it is proposed that exposure to Th2-driven inflammation enhances the overexpression of the POSTN gene, resulting an increased level of periostin21. In addition, IL-13 may induce release of periostin from bronchial epithelial cells32. S1P is known to be associated with airway hyperactivity and Th2 cytokines in mouse lung101133.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms of periostin in AERD are not fully understood, it is proposed that exposure to Th2-driven inflammation enhances the overexpression of the POSTN gene, resulting an increased level of periostin21. In addition, IL-13 may induce release of periostin from bronchial epithelial cells32. S1P is known to be associated with airway hyperactivity and Th2 cytokines in mouse lung101133.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression is elevated in human bronchial epithelial cells in association with increased expression of IL-5 and IL-13 in the submucosa (44,45). Serum periostin is a better predictor of airway eosinophilia in SA than FeNO is, although blood eosinophils are also reasonably predictive (46,47). Therefore, it is not yet clear which biomarker will best identify Type-2 immune-inflammation in SA.…”
Section: Inflammatory Processes: Pathobiological Evidence For Type-2 mentioning
confidence: 99%
“…Recent studies have suggested that periostin modulates Th2-mediated asthma pathogenesis by assisting in the recruitment of inflammatory cells, particularly eosinophils, to the lungs [34]. Moreover, periostin is known to facilitate the activation of dendritic cells, thereby rendering airway hyperresponsiveness and airway inflammation in mice [35, 36]. Beside, we discovered an increased serum level of MPO in the ABCC4 −1508G allele carriers comparing to that of noncarriers.…”
Section: Discussionmentioning
confidence: 67%